Care of long-term survivors of head and neck cancer after treatment with oral or facial prostheses, or both. Issue 7 (September 2017) - Worrell, E.; Worrell, L.; Bisase, B.
Abstract: The current evidence of good practice in the delivery of long-term supportive care to patients who have been treated for head and neck cancer is sparse. We recruited 10 survivors so that we could follow their experience after their acute treatment was over. There were six men (mean (range) age 72 (54-86) years) and four women (mean (range) age 69 (67-73) years). After ethics committee approval had been given, we used structured interviews and questionnaires to investigate the impact of the resection and reconstruction, the patients' perceived needs, and their use of supportive care services. Their experiences were in line with current treatment of head and neck cancer. Whether they would survive the cancer was an initial fear (up to a year postoperatively), and some subjects reported problems more than five years after treatment, particularly with swallowing, quality of saliva, and intelligible speech. This small group of survivors of head and neck cancer maintained a good quality of life physically, socially, and emotionally. Limitations were put down to their age rather than their diagnosis of cancer or their rehabilitation. Analysis of their perceived needs showed that supportive care services were readily available and were valued by the patients, and that all their needs were met.